CATALYZING FEMALE ENTREPRENEURSHIP: HRM PRACTICES AND DIGITAL TECHNOLOGY UTILIZATION IN INDONESIA'S DIVERSE BUSINESS ENVIRONMENT - Diah Fatma Sjoraida; Nyoman Dwika Ayu Amrita; Arif Budi Raharja (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Abstract Women's entrepreneurship and the use of digital technology have an increasingly important role in driving inclusive and sustainable economic growth in Indonesia. In diverse business contexts, inclusive human resource management (HRM) practices play a crucial role in supporting women's entrepreneurship. Through special training programs, work flexibility policies, and performance-based promotions, women can more easily manage their businesses with independence and confidence. In addition, the use of digital technology, such as e-commerce and business management applications, has had a positive impact on the growth and efficiency of women's businesses. Through e-commerce, women can expand their market online, while business management applications enable them to manage daily operations more efficiently. However, challenges such as the digital divide and patriarchal culture remain obstacles in optimizing the potential of women's entrepreneurship and digital technology. Therefore, collaboration between the government, private sector and NGOs is very important in strengthening support for women's entrepreneurship and the use of digital technology. The government can create a supportive policy framework, while the private sector can provide market access, business capital and user-friendly digital technology. NGOs, on the other hand, can provide training, mentorship, and advocacy for policies that support women's entrepreneurship. By collaborating effectively, various parties can create a supportive ecosystem for women entrepreneurs and accelerate the transformation towards an inclusive digital economy in Indonesia.